1996
DOI: 10.1002/(sici)1097-0320(19960601)24:2<167::aid-cyto9>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Bull sperm head morphometry related to abnormal chromatin structure and fertility

Abstract: This study investigated the relationship between morphologically abnormal sperm, sperm chromatin structure, and fertility. Semen samples were obtained from 13 bulls. The sperm chromatin structure assay (SCSA), a sensitive measure of denaturability of sperm nuclear DNA in situ following acid treatment, was performed on each sample to quantitate abnormal chromatin structure. Feulgenstained sperm head morphology was measured by computerized image analysis (ONCOR-Image): Sixteen parameters were measured for each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
0
13
0
3
Order By: Relevance
“…It is known that aging induces apoptosis in the epididymis, which seems to be caused by the fall of testosterone levels and is probably related to an increase of oxidative stress in tissues (Jara et al, 2004). It has been stated by Sailer et al (1996) that abnormal chromatin structure may lead to problems in sperm nuclear packaging material, which can be related to morphologically abnormal spermatozoa. This was noticed in our study with respect to young boars, but not in old boars; SCI was also at a high level in this group.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that aging induces apoptosis in the epididymis, which seems to be caused by the fall of testosterone levels and is probably related to an increase of oxidative stress in tissues (Jara et al, 2004). It has been stated by Sailer et al (1996) that abnormal chromatin structure may lead to problems in sperm nuclear packaging material, which can be related to morphologically abnormal spermatozoa. This was noticed in our study with respect to young boars, but not in old boars; SCI was also at a high level in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Further, any subtle changes in sperm chromatin condensation or alteration in sperm histone-protamine ratio necessary for chromatin packing may directly reflect in changes in head morphology and morphometry [10]. Experimental studies have demonstrated a positive correlation between abnormal sperm head morphology and DNA damage and chromatin integrity, but such relationship in infertile patients was not extensively studied [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…É oportuno salientar que o corante AA é mais frequentemente utilizado para avaliações com citofotômetro de fluxo (Evenson et al, 1980, Sailer et al, 1996Ostermeier et al, 2001) e que, neste trabalho, os esfregaços corados com AA foram avaliados em microscopia de fluorescência (Tejada et al, 1984;Hamamah et al, 1990;Erenpreiss et al, 2001). O citofotômetro permite uma avaliação objetiva e rápida.…”
Section: Resultsunclassified
“…A cabeça dos espermatozóides dos mamíferos é quase que totalmente constituída de cromatina, portanto espera-se que alterações em tais estruturas sejam acompanhadas por anomalias morfológicas (Sailer et al, 1996;Ferrari et al, 1998;Ostermeier et al, 2001;Beletti et al, 2005).…”
Section: Introductionunclassified